Early diversifications of angiosperms and their insect pollinators: were they unlinked?. (September 2022) - Asar, Yasmin; Ho, Simon Y.W.; Sauquet, Hervé
Abstract : The present-day ubiquity of angiosperm-insect pollination has led to the hypothesis that these two groups coevolved early in their evolutionary history. However, recent fossil discoveries and fossil-calibrated molecular dating analyses challenge the notion that early diversifications of angiosperms and insects were inextricably linked. In this article, we examine (i) the discrepancies between dates of emergence for angiosperms and major clades of insects; (ii) the long history of gymnosperm–insect pollination modes, which likely shaped early angiosperm–insect pollination mutualisms; and (iii) how the K–Pg (Cretaceous–Paleogene) mass extinction event was vital in propelling modern angiosperm–insect mutualisms. We posit that the early diversifications of angiosperms and their insect pollinators were largely decoupled until the end of the Cretaceous. Highlights: The past decade has seen the discovery of many fossils of Mesozoic insects that pollinated gymnospermous plants. Much insect family diversity accumulated early in the evolutionary history of the group and plateaued during the Cretaceous, conflicting with the idea of a 'Cretaceous Terrestrial Revolution'. Recent fossil-calibrated molecular dating studies have found that the emergence of insect pollinator clades did not coincide with the initial emergence and diversification of angiosperms. The Cretaceous–Paleogene mass extinction event significantly altered the global landscape, resulting in the formation of modern tropical rainforests and the decline of gymnospermous forests. These angiosperm-dominated rainforests supported the emergence of megadiverse insect communities.